Salvia miltiorrhiza-Containing Chinese Herbal Medicine Combined With GnRH Agonist for Postoperative Treatment of Endometriosis: A Systematic Review and meta-Analysis - Gao, Qiang; Shen, Lei; Jiang, Bei; Luan, Yi-feng; Lin, Li-na; Meng, Fan-ci; Wang, Chao-ying; Cong, Hui-fang (Frontiers in Pharmacology, 2022)
Background: Endometriosis is an estrogen-dependent gynecological inflammatory condition that may lead to infertility and recurrent pelvic pain. The purpose of this research was to determine the efficacy and safety of Salvia-containing Chinese herbal medicine (CHM) combined with gonadotropin-releasing hormone agonist (GnRH-a) for postoperative endometriosis management. Methods:Eight databases were systematically searched before October 2021, including PubMed, Embase, Cochrane Library, Scopus, Web of Sceince, CNKI, VIP, and Wanfang. Finally, all randomized controlled studies comparing Salvia-containing CHM paired with GnRH-a to GnRH-a alone for postoperative endometriosis management were included. Results: A total of 10 trials involving 836 patients were reported and analyzed. Compared with the control group, the Salvia-containing CHM combined with GnRH-a group showed significant superiority in decreasing endometriosis recurrence (risk ratio [RR] = 0.26; 95 % confidence intervals [CI]: 0.16 to 0.41) and increasing the pregnancy rate ([RR] = 1.96; 95% CI: 1.58 to 2.44). Similarly, the effect of the Salvia-containing CHM combined with GnRH-a on CA-125 serum levels was positive (standardized mean difference [SMD] = -0.79; 95% CI: -1.11 to -0.47) . Furthermore, this group showed a significant reduction in adverse effects. Conclusion: The results indicate that Salvia-containing CHM may be a viable choice for postoperative endometriosis therapy, with the potential to enhance pregnancy while decreasing recurrence and adverse effects.